Enhanced photocatalytic characteristics of Ag-Cu\(_2\)O nanocomposites synthesized via one-pot method for polluted water treatment - Dao, Phi Hung; Nguyen, Tien Dung; Nguyen, Thuy Chinh; Trinh, Thanh Huyen; Vu, Dinh Hieu; Thai, Hoang (Communications in Physics, 2024)
The paper presents results of synthesizing Ag-Cu2O nanocomposites by one pot method. The characteristics, properties of Ag-Cu2O nanocomposites were determined by X ray diffraction, Field Emission Scanning Electron Microscopy (FESEM) and UV-Vis diffuse reflectance spectroscopy. The obtained results indicated that the crystalline size of Cu2O particles was about 38.36 nm while that of Ag particles was about 12 nm. The FESEM images showed tendency of agglomeration of Cu2O particles. The Ag nanoparticles were dispersed regularly on the surface of Cu2O particles. Due to modification by AgNO3 salt solution, the Ag-Cu2O nanocomposites had a better ability to absorb light than the Cu2O particles and had a lower bandgap energy. Additionally, the Ag-Cu2O nanocomposites also had a higher photocatalytic activity than that of the Cu2O particles. The Ag-Cu2O nanocomposite is promising for water treatment application